Assessing industry 4.0 readiness: a TOE-P framework for the sugar industry in developing economies - Satish Chandra Pandey; Naveen Virmani; Divya Choudhary; Sandeep Jagtap (Discover Sustainability)
Abstract Industry 4.0 concepts have recently significantly supported transparency and reliability in every industrial sector. Organizations must adapt their traditional paradigms and approaches to align with market demands. Hence, developing a framework that can change these conventional approaches with fresh ideas is essential. The Industry 4.0 (I4.0) readiness model presents a creative concept that holds promise for the entire organizational and industrial value chain. Existing research focused only on technological, organizational, and environmental aspects. However, in process-extensive industries, like the sugar sector, the process is critical and considerably impacts the business. So, providing a strong framework for such sectors is necessary. The novelty of this paper is putting a process dimension in the TOE framework, which is critical for sugar industries. The study develops the extended framework to assess readiness. Experts have validated the framework as the study enhances it by adding process dimensions. Practitioners can apply the modeling concept to study the readiness framework in various sectors. Consequently, essential findings and recommendations drive the discussion forward. The study highlights opportunities for cross-disciplinary research across sectors.